ISOLASI DAN KARAKTERISASI MIKORIZA VESIKULAR-ARBUSKULAR DI LAHAN KERING MASAM, LAMPUNG TENGAH - Prihastuti (The East Java Biological Society, 2007)
This research aimed to determine spore of vesicular-arbuscular mycorrhizae collected from acid dry land of Central Lampung. The character of research was descriptive-explorative. Soil samples were collected by stratified random sampling method. The results indicated that amount of spore at rizospher area reached 33-311 spores/g of soil. There were 8 forms of mycorrhizae spores. The species of mycorrhizae found were Gigaspora margarita, Glomus moseae, Glomus versiforme, Acaulospora sp., Endogone piriformis, Smilacina racemosa, Entrophospora sp. and Scutellospora sp. Further research is needed for the exploitation land improvement of the effectiveness of natural mycorrhizae on acid dry land at Central Lampung.